Endorectal MRI and MR spectroscopic imaging of prostate cancer: Developing selection criteria for MR‐guided focal therapy. Issue 3 (16th May 2013) - Chang, Stephanie T.; Westphalen, Antonio C.; Jha, Priyanka; Jung, Adam J.; Carroll, Peter R.; Kurhanewicz, John; Coakley, Fergus V.
Abstract : Purpose: To investigate criteria that can identify dominant treatable prostate cancer foci with high certainty at endorectal magnetic resonance imaging (MRI) and MR spectroscopic (MRS) imaging, and thus facilitate selection of patients who are radiological candidates for MR‐guided focal therapy. Materials and Methods: We retrospectively identified 88 patients with biopsy‐proven prostate cancer who underwent endorectal MRI and MRS imaging prior to radical prostatectomy with creation of histopathological tumor maps. Two independent readers noted the largest tumor foci at MRI, if visible, and the volume of concordant abnormal tissue at MRS imaging, if present. A logistic random intercept model was used to determine the association between clinical and MR findings and correct identification of treatable (over 0.5 cm 3 ) dominant intraprostatic tumor foci. Results: Readers 1 and 2 identified dominant tumor foci in 50 (57%) and 58 (65%) of 88 patients; 42 (84%) and 48 (83%) of these were dominant treatable lesions at histopathology, respectively. Within the statistical model, the volume of concordant spectroscopic abnormality was the only factor that predicted correct identification of a dominant treatable lesion on T2‐weighted images (odds ratio = 1.75; 95% confidence interval = 1.08 to 2.82; P value = 0.02). In particular, all visible lesions on T2‐weighted imaging associated with at least 0.54 cm 3 of concordant spectroscopic abnormality were correctly identified dominant treatable tumor foci. Conclusion: Patients with dominant intraprostatic tumor foci seen on T2‐weighted MRI and associated with at least 0.54 cm 3 of concordant MRS imaging abnormality may be radiological candidates for MR‐guided focal therapy.J. Magn. Reson. Imaging 2014;39:519–525 . ©2013 Wiley Periodicals, Inc.